Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures